2014
DOI: 10.1016/j.placenta.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the human placenta transcriptome

Abstract: As the conduit for nutrients and growth signals, the placenta is critical to establishing an environment sufficient for fetal growth and development. To better understand the mechanisms regulating placental development and gene expression, we characterized the transcriptome of term placenta from 20 healthy women with uncomplicated pregnancies using RNA-seq. To identify genes that were highly expressed and unique to the placenta we compared placental RNA-seq data to data from 7 other tissues (adipose, breast, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 34 publications
3
62
1
Order By: Relevance
“…CGA, CGB, CSH1, ERVWE1, HSD3B1 ) expression [7277], while the L1PA6 TE in the LGALS16 5’UTR is not enriched by these binding sites. In addition, the human LGALS13 , LGALS14 and LGALS16 promoters contain putative binding sites for GATA, TEF-5 and ESRRG, which latter is important in the regulation of trophoblast metabolism [78,79].…”
Section: Resultsmentioning
confidence: 99%
“…CGA, CGB, CSH1, ERVWE1, HSD3B1 ) expression [7277], while the L1PA6 TE in the LGALS16 5’UTR is not enriched by these binding sites. In addition, the human LGALS13 , LGALS14 and LGALS16 promoters contain putative binding sites for GATA, TEF-5 and ESRRG, which latter is important in the regulation of trophoblast metabolism [78,79].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomics embraces the quantitative study of the expression levels of mRNAs utilizing microarray and RNA-seq technologies. The transcriptome of placentas from normal pregnancies has been characterized [15] and significant changes occur in pregnancies compromised by antiphospholipid antibodies [16] and by maternal cigarette smoking [17].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…First, it is the only family member (besides ZFP36L3) for which a deficiency is known to cause defects in the mouse placenta, leading to failure of chorioallantoic fusion (Stumpo et al, 2004). Second, deep sequencing experiments have shown that its mRNA levels are the highest of the three family members found in human placenta (Saben et al, 2014). Finally, Zfp36l1 mRNA is the most highly expressed of the family members in the placentas from the rodent Nannospalax galili, a species very close evolutionarily to the rodents that express ZFP36L3, but which apparently does not express ZFP36L3 in the placenta (Gingerich et al, 2016).…”
Section: Discussionmentioning
confidence: 99%